Implikasi Pencabutan Hak Politik Sebagai Pidana Tambahan Bagi Terpidana Korupsi - Dennis Efraim (Universitas Widya Gama Malang, 2021)
The main problem of this research is that there are many corruption cases in Indonesia by public officials. In the corruption case that occurred, it turned out that the Supreme Court had once imposed an additional sentence for the convict in the form of revocation of his political rights. The judge assessed that efforts to revoke political rights were carried out because corruption was considered to damage the principles of national and state life, gave a bad image to the pillars of democracy, had the potential to disrupt the people's economy and state finances, thereby disrupting the continuity and development of the country. The approach method used in this research is juridical normative with secondary data collection methods in the form of primary and secondary legal materials. The results showed: first, deprivation of political rights does not violate human rights but its implementation can be limited based on law, to guarantee recognition and respect for human rights and the basic freedoms of others, morals, public interest, and national interest; second, the implementation of political rights revocation will close the opportunity for the convict to show his role again as a member of society, so the handling of corruption crimes should no longer focus solely on penal policies, but through non-penal policies which have a strategic role by strengthening the supervision of the Corruption Eradication Commission and building transparency in every element of government in order to prevent corruption practices itself.AbstrakMasalah utama dari penelitian ini adalah masih banyaknya kasus korupsi di Indonesia oleh pejabat publik.Dalam kasus korupsi yang terjadi,ternyata Mahkamah Agung pernah menjatuhkan hukuman tambahan bagi terpidana berupa pencabutan politiknya hak.Hakim menilai upaya pencabutan hak politik dilakukan karena korupsi dianggap merusak prinsip kehidupan berbangsa dan bernegara, memberikan citra buruk hingga pilar demokrasi,berpotensi mengganggu perekonomian dan negara rakyat keuangan,sehingga mengganggu kelangsungan dan pembangunan negara.Pendekatan Metode yang digunakan dalam penelitian ini adalah yuridis normatif dengan metode pengumpulan data sekunder di PT bentuk bahan hukum primer dan sekunder.Hasilnya menunjukkan: pertama, perampasan hak politik tidak melanggar hak asasi manusia tetapi penerapannya dapat dibatasi berdasarkan hukum,untuk menjamin pengakuan dan penghormatan terhadap hak asasi manusia dan kebebasan dasar orang lain,moral, kepentingan umum, dan kepentingan nasional; kedua, implementasi hak politik pencabutan akan menutup kesempatan terpidana untuk kembali berperan sebagai anggota masyarakat,sehingga penanganan tindak pidana korupsi seharusnya tidak lagi fokus pada kebijakan pidana semata,tetapi melalui kebijakan non penal yang memiliki peran strategis dengan memperkuat pengawasan Komisi Pemberantasan Korupsi dan membangun transparansi di setiap elemen pemerintahan untuk mencegah praktik korupsi itu sendiri.